Impacts of Electricity Rates on the Economics of Rooftop PV System - Raji, Atanda (International Journal of Advanced Research in Engineering, 2016)
The huge negative environmental impacts of using fossil fuel-based electricity generation systems is widely visible in terms of air pollutions, greenhouse gas emissions induced climate change, and skyrocketing of electricity prices while the resource is continuously being depleted. Using renewable energy source such as solar energy will surely reduce the negative impacts of conventional fuels used for electricity generation. Mitigating the negative impact of the traditional energy sources usage for the production of electricity needs a concerted effort of all inhabitants of the planet Earth. Renewable energy sources such as wind and solar have recently been seen as saviours. While the technical possibility and their readiness are seen as non-barriers to their deployment, one major barrier that recently has been showing up is the economical comparison of their economics with grid electricity where and when it is available. The premium is still acceptable for having a standalone PV system where grid electricity is not reachable. The economics analysis of such standalone system can easily been computed as there are less dynamics involved. The case is a bit complicated where the PV system is grid-tied and bidirectional energy exchange with the grid is allowable. Dynamics such as feed-in tariffs, time of use tariffs, block tariffs et cetera makes the economics analysis of grid-tied energy systems complicated to model, analyse, and optimise. Net present cost as an economic indicator of technical feasible grid-tied energy system is used to assess the economic viability using HOMER software. Different scenarios are evaluated with fixed electricity rate but with different sellback prices.